PENGARUH OBJEKTIVITAS, AKUNTABILITAS, INTEGRITAS DAN PROFESIONALISME TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik di Wilayah Jakarta Selatan) - Rahmatika Novia; Andreas Andreas; L Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the Effect of Objectivity, Accountability, Integrity and Professionalism on Audit Quality (Empirical Study of Public Accounting Firms in South Jakarta). The sample was determined by convenience sampling method. In order to obtain 155 samples of auditors who were respondents. This study uses primary data obtained from respondents' answers and distributed questionnaires. The collected data were analyzed using data analysis methods by first proposing classical assumptions before testing the hypothesis. Classic assumption tests and hypothesis testing were carried out using SPSS version 22 software. The results of this study concluded that Objectivity has a significant effect on Audit Quality, Accountability has a significant effect on Audit Quality, Integrity has a significant effect on Audit Quality, and Professionalism has a significant positive effect on Audit Quality.Keywords:Objectivity, Accountability, Integrity, Professionalism, Audit Quality